Biotinidase Deficiency in Newborns as Respiratory Distress and Tachypnea: A Case Report - KOOHMANAEE, Shahin; ZARKESH, Marjaneh; TABRIZI, Manijeh; HASSANZADEH RAF, Afagh; DIVSHALI, Siamak; DALILI, Setila (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Kohmanaee Sh, Zarkesh M, Tabrizi M, Hassanzadeh Rad A, Divshali S, Dalili S. Biotinidase Deficiency in Newborns as Respiratory Distress and Tachypnea: A Case Report. Iran J Child Neurol. Spring 2015; 9(2):58-60. Abstract Objective Biotin is a coenzyme composed of four carboxylases. It presents in amino acid catabolism, fatty acid synthesis, and gluconeogenesis. Biotinidase recycles the vitamin biotin. A biotinidase deficiency is a neurocutaneous disorder with autosomal recessive inheritance. The symptoms can be successfully treated or prevented by administering pharmacological doses of biotin. Although, according to neonatal prenatal medicine (2011), a biotinidase deficiency does not manifest during the neonatal period. In this study, we report on a case of biotinidase deficiency in the first week of birth. Case Report A 3100 g term boy was born via cesarean section. After 3 days, he was referred to the 17th Shahrivar Hospital with the chief complaint of tachypnea and grunting. Laboratory results revealed that liver and renal function tests, serum electrolytes, and blood indexes except ammonia were all normal. Within few days after the administration of oral biotin, the patient showed dramatic improvement and was discharged. However, within 4 months he was admitted two other times with the complaints of diarrhea and pneumonia. Unfortunately, he expired after 4 months. Conclusion According to our results, it seems that clinicians should accurately assess suspicious patients and even assess infants for biotinidase deficiency.